2021
DOI: 10.1017/s1368980021004808
|View full text |Cite
|
Sign up to set email alerts
|

Association between iron supplementation and the presence of diarrhoea in Peruvian children aged 6–59 months: analysis of the database of the Demographic and Family Health Survey in Peru (DHS, Peru), years 2009–2019

Abstract: Introduction: According to the World Health Organization (WHO), anemia is a severe public health problem when the prevalence is ≥ 40%. In 2019, in Peru, 40.1% of children (age 6 to 35 months) are diagnosed as anemic. This is a concern since, despite the efforts of the governments to reduce the prevalence, the problem has stagnated since 2011. The treatment applied to deal with anemia is iron supplementation. Although iron is essential for cell function, an excess can produce adverse responses, such as gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Despite the fact that the main side effect of ferric citrate was gastrointestinal [29], there was no appreciable difference in the adverse effects of constipation between the ferric citrate, placebo, or active treatment [30]. Simultaneously, other studies had found that iron-induced diarrhea was associated with an inflammatory response caused by intestinal flora, which usually occurred early in treatment and was mild [31]. Iron citrate reduces anemia by raising the serum iron reserve and suppressing FGF-23 production, which might contribute to cardiovascular remodeling [32, 33], in addition to lowering blood phosphate by decomposing ferric ions (Fe3+) and interacting with phosphate [12, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that the main side effect of ferric citrate was gastrointestinal [29], there was no appreciable difference in the adverse effects of constipation between the ferric citrate, placebo, or active treatment [30]. Simultaneously, other studies had found that iron-induced diarrhea was associated with an inflammatory response caused by intestinal flora, which usually occurred early in treatment and was mild [31]. Iron citrate reduces anemia by raising the serum iron reserve and suppressing FGF-23 production, which might contribute to cardiovascular remodeling [32, 33], in addition to lowering blood phosphate by decomposing ferric ions (Fe3+) and interacting with phosphate [12, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that excessive iron supplementation would damage the intestinal immune system of infants increasing the risk of diarrhea and lead to increased iron content in the hippocampus damaging social cognition, etc. [ 6,7 ] Besides, excessive iron intake would antagonize the absorption of copper in the diet, finally affecting copper homeostasis in the body. [ 8,9 ] Thus, maintaining iron homeostasis in infants during suckling is important.…”
Section: Introductionmentioning
confidence: 99%